Characterizing the Impact of Fabrication Methods on Mechanically Tunable Gelatin Hydrogels for Cardiac Fibrosis Studies - Jordyn Folh; Phan Linh Dan Tran; Renita E. Horton (Bioengineering)
The mechanical properties of the extracellular matrix critically influence cell behavior in both physiological and pathophysiological states, including cardiac fibrosis. In vitro models have played a critical role in assessing biological mechanisms. In this study, we characterized mechanically tunable enzymatically crosslinked gelatin-microbial transglutaminase (mTG) hydrogels for modeling cardiovascular diseases. Gelatin hydrogels were fabricated via direct mixing or immersion crosslinking methods. Hydrogel formulations were assessed using the Piuma nanoindenter and Instron systems. This study investigates the effects of fabrication methods, UV ozone (UVO) sterilization, crosslinking methods, and incubation media on hydrogel stiffness. Further, this study examined the response of murine cardiac fibroblasts to hydrogel stiffness. The hydrogels exhibited modulus ranges relevant to both healthy and fibrotic cardiac tissues. UVO exposure led to slight decreases in hydrogel modulus, while the fabrication method had a significant impact on the modulus. Hydrogels incubated in phosphate buffered saline (PBS) were stiffer than those incubated in Medium 199 (M199), which correlated with lower pH in PBS. Fibroblasts cultured on stiffer hydrogels display enhanced smooth muscle actin (SMA) expression, suggesting sensitivity to material stiffness. These findings highlight how fabrication parameters influence the modulus of gelatin-mTG hydrogels for cardiac tissue models.